2014
DOI: 10.1016/j.cortex.2013.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Latent information in fluency lists predicts functional decline in persons at risk for Alzheimer disease

Abstract: Objective We constructed random forest classifiers employing either the traditional method of scoring semantic fluency word lists or new methods. These classifiers were then compared in terms of their ability to diagnose Alzheimer disease (AD) or to prognosticate among individuals along the continuum from cognitively normal (CN) through mild cognitive impairment (MCI) to AD. Method Semantic fluency lists from 44 cognitively normal elderly individuals, 80 MCI patients, and 41 AD patients were transcribed into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 51 publications
(56 reference statements)
3
42
1
1
Order By: Relevance
“…Other biomarkers to detect AD and MCI included semantic fluency and eye movement. Clark et al constructed random forest classifiers using latent information in semantic fluency word lists to predict cognitive and functional decline (28). Lagun et al.…”
Section: Resultsmentioning
confidence: 99%
“…Other biomarkers to detect AD and MCI included semantic fluency and eye movement. Clark et al constructed random forest classifiers using latent information in semantic fluency word lists to predict cognitive and functional decline (28). Lagun et al.…”
Section: Resultsmentioning
confidence: 99%
“…A similarly semantic, but somehow even more abstract mechanism, was recently reported in the longitudinal characterisation of the painting skills of a Chinese painter, who showed a progressive impoverishment in his work, concurrent with the progression of AD [16]. These studies are accompanied by other research that has looked at latent aspects of lexical performance in the spectrum from normal ageing to MCI and AD [17,18]. This latter research has shown that older adults outperformed people with clinical AD, its prodromal MCI stage and also young controls in category fluency, producing more words which are later acquired, less typical and less familiar [18].…”
mentioning
confidence: 94%
“…Most recently, support vector regression was used to predict OCD severity from brain structural magnetic resonance imaging (MRI) data (Hoexter et al ., 2013). Random Forests (RF), another machine learning algorithm, has been less widely used in clinical medicine and has seen very little application in neuroimaging or other psychiatric research (see exceptions: Tektonidou et al ., 2011; Arnold et al ., 2012; Gibbons et al ., 2013; Clark et al ., 2014). To our knowledge, RF has not yet been applied to predict remission outcomes in longitudinal psychiatric samples nor to analyze data in anxiety disorder samples.…”
Section: Introductionmentioning
confidence: 99%